HUBUNGAN FAKTOR INDIVIDU DAN KETERSEDIAAN PROSEDUR PERAWATAN MESIN DENGAN TINDAKAN TIDAK AMAN OLEH MEKANIK - Nurlita Wulansari; Denny Ardyanto W. (Universitas Airlangga, 2019)
Container loading and unloading activities are categorized high risk, because the equipment used is a lifting plane for heavy lifting. Based on the results of observations, a work accident caused due to unsafe actions. According to ILCI theory, unsafe actions are caused by management factors (availability of machine maintenance procedures) and individual factors (age, education, employment and knowledge) of workers. The design of this research was cross-sectional. The samples of this study were 35 workers from the total population of 43 mechanical workers of lifting aircraft. The samples were taken from mechanics included in the inclusion criteria of HMC mechanical workers (Harbour Mobile Crane). The data were obtained through observation and filling questionnaires to workers. Data were analyzed statistically by using spearman test. The statistic test results showed that there was no relationship between age with unsafe actions is 0.217, and for knowledge with unsafe action there was a relationship is 0.000. There was a relationship between the working period and the unsafe actions is 0.002. There was an relationship between the availability of the machine maintenance procedure and the unsafe actions is 0.019. With α <0.05. The conclusion is that not all individual factors were associated with unsafe actions, but the availability of machine maintenance procedures were associated with them. The program from the management to the safety and health of the worker should be reviewed periodically to enable workers to work safely and reduce occupational accidents.Keywords: loading and unloading containers, mechanics, unsafe actions